Legitimation Strategies as Valuable Signals in Nonfinancial Reporting? Effects on Investor Decision-Making - Hahn, Rüdiger; Reimsbach, Daniel; Kotzian, Peter; Feder, Madeleine; Weißenberger, Barbara E. (Business & Society)
Companies disclosing negative aspects in sustainability reports often employ legitimation strategies to present mishaps in a favorable light. In incentivized experiments, we find that nonprofessional investors divest from companies with a negative sustainability-related incident, and that symbolic legitimation (which only evasively explains a negative incident) is not a strong enough signal to counter this divestment behavior. Even substantial legitimation (which reports on measures and behavioral change) mitigates the divestment decisions only if the company reports on concrete remediation actions in morally charged situations, such as social or environmental incidents. We elaborate these results in light of signaling and screening theory, and suggest the conceptual extension of “costly signals” to what we call “valuable signals.” We argue that valuable signals need be not only costly for the sender from an economic perspective but also perceived as appropriate by the receiver from a noneconomic perspective.
Keywords: Social Sciences (miscellaneous); Business; Management and Accounting (miscellaneous)

The Personal Is Theoretical and the Past Is Present: Blurring the Lines in Contemporary Anti-Racist Writing - Hartmann, Alexandra (Open Cultural Studies)
Abstract This article studies the anti-racist writings by contemporary scholars Cornel West, Eddie S. Glaude, Jr., George Yancy, and Claudia Rankine. It uncovers how they include personal narratives in their works in order to theorise the workings of white hegemony in the twenty-first century. In doing so, I argue, they productively blur the lines between the personal and the theoretical as well as between the past and the present. Consequently, they problematise the notion of abstract theorising, the myth of continuous racial progress as well as conceptions of postracialism.
Keywords: General Social Sciences; General Arts and Humanities

Reflexive anthropomorphism: Ontological ignorance, or ignorant ontology? - Klowait, Nils (Sociological Journal)
Keywords: General Social Sciences

Social Impact Bonds und der Disput um die Wohlfahrt - Knoll, Lisa (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie)
Keywords: Sociology and Political Science; Social Psychology

The Personal Is Theoretical and the Past Is Present: Blurring the Lines in Contemporary Anti-Racist Writing - Hartmann, Alexandra (Open Cultural Studies)
Abstract This article studies the anti-racist writings by contemporary scholars Cornel West, Eddie S. Glaude, Jr., George Yancy, and Claudia Rankine. It uncovers how they include personal narratives in their works in order to theorise the workings of white hegemony in the twenty-first century. In doing so, I argue, they productively blur the lines between the personal and the theoretical as well as between the past and the present. Consequently, they problematise the notion of abstract theorising, the myth of continuous racial progress as well as conceptions of postracialism.
Keywords: General Social Sciences; General Arts and Humanities

Reciprocation Effort Games - Polevoy, Gleb; de Weerdt, M.M. (Proceedings of the 29th Benelux Conference on Artificial Intelligence)
Keywords: interaction; reciprocation; contribute; shared effort; curbing; convergence; threshold; Nash equilibrium; social welfare; efficiency; price of anarchy; price of stability

Competition between Cooperative Projects - Polevoy, Gleb; de Weerdt, M.M. (Proceedings of the 29th Benelux Conference on Artificial Intelligence)
Keywords: agents; projects; contribute; shared effort game; competition; quota; threshold; Nash equilibrium; social welfare; efficiency; price of anarchy; price of stability

Effects of additional knowledge of results on modifying highly practiced acyclic swimming techniques with knowledge of performance - Krause, Daniel (International Journal of Sports Science & Coaching)
The author investigated the effects of additional knowledge of results on modifying swimming starts and turns with video-based knowledge of performance. A total of 18 swimming experts (15–18 years of age) learned modifications of start and turn techniques with knowledge of performance or a combination of knowledge of performance and knowledge of results. The feedback condition was switched between the groups from experiment 1 to experiment 2. Both experiments contained 50 trials with augmented feedback distributed over five sessions. Both experiments revealed no detrimental effects of additional knowledge of results on process-related performance variables. With respect to the result-related variables (start time and turn time), only the groups without knowledge of results exhibited temporary impairment in the immediate retention tests. The results are largely replicated in both experiments. Knowledge of results seems to have positive effects on modifying with knowledge of performance. The presence of knowledge of results might reduce the deautomatizing conscious control processes that are induced by knowledge of performance and might cause temporary performance impairments.
Keywords: Social Sciences (miscellaneous)

The Game of Reciprocation Habits - Polevoy, Gleb; de Weerdt, M.M.; Jonker, C.M. (Proceedings of the 2016 European Conference on Artificial Intelligence)
Keywords: agents; action; repeated reciprocation; fixed; floating; network; Nash equilibrium; social welfare; price of anarchy; price of stability; convex combination

Acoustic Microphone Geometry Calibration: An overview and experimental evaluation of state-of-the-art algorithms - Plinge, Axel; Jacob, Florian; Haeb-Umbach, Reinhold; Fink, Gernot A. (IEEE Signal Processing Magazine)
Today, we are often surrounded by devices with one or more microphones, such as smartphones, laptops, and wireless microphones. If they are part of an acoustic sensor network, their distribution in the environment can be beneficially exploited for various speech processing tasks. However, applications like speaker localization, speaker tracking, and speech enhancement by beamforming avail themselves of the geometrical configuration of the sensors. Therefore, acoustic microphone geometry calibration has recently become a very active field of research. This article provides an application-oriented, comprehensive survey of existing methods for microphone position self-calibration, which will be categorized by the measurements they use and the scenarios they can calibrate. Selected methods will be evaluated comparatively with real-world recordings.
Keywords: Acoustic sensors; Microphones; Portable computers; Smart phones; Wireless communication; Wireless sensor networks

An Alternative to Mapping a Word onto a Concept in Language Acquisition: Pragmatic Frames - Rohlfing, Katharina; Wrede, Britta; Vollmer, Anna-Lisa; Oudeyer, Pierre-Yves (FRONTIERS IN PSYCHOLOGY)
The classic mapping metaphor posits that children learn a word by mapping it onto a concept of an object or event. However, we believe that a mapping metaphor cannot account for word learning, because even though children focus attention on objects, they do not necessarily remember the connection between the word and the referent unless it is framed pragmatically, that is, within a task. Our theoretical paper proposes an alternative mechanism for word learning. Our main premise is that word learning occurs as children accomplish a goal in cooperation with a partner. We follow Bruner's (1983) idea and further specify pragmatic frames as the learning units that drive language acquisition and cognitive development. These units consist of a sequence of actions and verbal behaviors that are co-constructed with a partner to achieve a joint goal. We elaborate on this alternative, offer some initial parametrizations of the concept, and embed it in current language learning approaches.
Keywords: language acquisition; pragmatics; infants' social learning; frames; learning and memory; developmental robotics

Tackling Complexity in Business and Society Research: The Methodological and Thematic Potential of Factorial Surveys - Oll, Josua; Hahn, Rüdiger; Reimsbach, Daniel; Kotzian, Peter (Business & Society)
Factorial surveys (FSs) integrate elements of survey research and classical experiments. Using a large number of respondents in a controlled setting, FSs approximate complex and realistic judgment situations through so-called vignettes—that is, carefully designed descriptions of hypothetical people, social situations, or scenarios. Despite being rooted, and predominantly applied, in sociology, FSs are particularly promising for business and society (B&S) scholars. Given the multiplicity, inherent complexity, and sometimes fuzziness of B&S research objects, conventional research methods inevitably reach their limits. This article, therefore, systematically presents methodological and thematic opportunities for FS studies in B&S research. It is argued that FSs are well suited to dealing with the complex interplay of societal-, organizational-, and individual-level factors in B&S research and to studying the principles underlying human perceptions, attitudes, values, social norms, and (anticipated) behavior. The application of the FS method is illustrated based on a showcase example in the realm of socially responsible investments (SRIs). As the literature on the conceptualization of FSs is limited, methodological challenges are addressed to guide B&S researchers past the common methodological pitfalls.
Keywords: Social Sciences (miscellaneous); Business; Management and Accounting (miscellaneous)

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

Over effective hard real-time hardware tasks scheduling and allocation - Guettatfi, Zakarya; Kermia, Omar; Khouas, Abdelhakim (25th International Conference on Field Programmable Logic and Applications (FPL))
Keywords: embedded systems; field programmable gate arrays; operating systems (computers); scheduling; μC/OS-II; FPGAs; OS foundation; SafeRTOS; Xenomai; chip utilization ration; complex time constraints; embedded systems; hard real-time hardware task allocation; hard real-time hardware task scheduling; hardware-software real-time operating systems; partially reconfigurable field-programmable gate arrays; resource constraints; safety-critical RTOS; Field programmable gate arrays; Hardware; Job shop scheduling; Real-time systems; Shape; Software

Alignment to the Actions of a Robot - Vollmer, Anna-Lisa; Rohlfing, Katharina; Wrede, Britta; Cangelosi, Angelo (International Journal of Social Robotics)
Alignment is a phenomenon observed in human conversation: Dialog partners' behavior converges in many respects. Such alignment has been proposed to be automatic and the basis for communicating successfully. Recent research on human-computer dialog promotes a mediated communicative design account of alignment according to which the extent of alignment is influenced by interlocutors' beliefs about each other. Our work aims at adding to these findings in two ways. (a) Our work investigates alignment of manual actions, instead of lexical choice. (b) Participants interact with the iCub humanoid robot, instead of an artificial computer dialog system. Our results confirm that alignment also takes place in the domain of actions. We were not able to replicate the results of the original study in general in this setting, but in accordance with its findings, participants with a high questionnaire score for emotional stability and participants who are familiar with robots align their actions more to a robot they believe to be basic than to one they believe to be advanced. Regarding alignment over the course of an interaction, the extent of alignment seems to remain constant, when participants believe the robot to be advanced, but it increases over time, when participants believe the robot to be a basic version.
Keywords: learning; Human-robot interaction; Alignment; Robot social; Action understanding

Signaling Competition and Social Welfare - Polevoy, Gleb; Smorodinsky, Rann; Tennenholtz, Moshe (ACM Trans. Econ. Comput.)
Keywords: Competition; efficiency; equilibrium; market; social welfare

Towards a Conceptualization of Online Community Health - Wagner, David; Richter, Alexander; Trier, Matthias; Wagner, Heinz-Theo (Proceedings of the 35th International Conference on Information Systems. ICIS 2014)
Along with the increasing popularity of social media and online communities in many business settings, the notion of online community health has become a common means by which community managers judge the condition or state of their communities. It has also been introduced to the literature, yet the concept remains underspecified and fragmented. In this paper, we work toward a construct conceptualization of online community health. Through a review of extant literature and dialogue with specialists in the field, we develop a multi-dimensional construct of online community health, consisting of seven elements. In writing this paper, we attempt to foster theory development around new organizational forms by advancing a new and important construct. The paper further provides guidance to the managers of social media and online communities by taking a systematic look at the well-being of their communities.
Keywords: Social media; Online communities; Online community success; Online community health; Construct conceptualization

Tutoring in adult-child-interaction: On the loop of the tutor's action modification and the recipient's gaze - Pitsch, Karola; Vollmer, Anna-Lisa; Rohlfing, Katharina; Fritsch, Jannik; Wrede, Britta (Interaction Studies)
Research of tutoring in parent-infant interaction has shown that tutors - when presenting some action - modify both their verbal and manual performance for the learner (‘motherese’, ‘motionese’). Investigating the sources and effects of the tutors’ action modifications, we suggest an interactional account of ‘motionese’. Using video-data from a semi-experimental study in which parents taught their 8 to 11 month old infants how to nest a set of differently sized cups, we found that the tutors’ action modifications (in particular: high arches) functioned as an orienting device to guide the infant’s visual attention (gaze). Action modification and the recipient’s gaze can be seen to have a reciprocal sequential relationship and to constitute a constant loop of mutual adjustments. Implications are discussed for developmental research and for robotic ‘Social Learning’. We argue that a robot system could use on-line feedback strategies (e.g. gaze) to pro-actively shape a tutor’s action presentation as it emerges.
Keywords: conversation analysis; interactional coordination; adult-child-interaction; feedback; gaze; quantification; social learning; motionese; tutoring

Infants' online perception of give-and-take interactions - Elsner, Claudia; Bakker, Marta; Rohlfing, Katharina; Gredebäck, Gustaf (Journal of Experimental Child Psychology)
This research investigated infants’ online perception of give-me gestures during observation of a social interaction. In the first experiment, goal-directed eye movements of 12-month-olds were recorded as they observed a give-and-take interaction in which an object is passed from one individual to another. Infants’ gaze shifts from the passing hand to the receiving hand were significantly faster when the receiving hand formed a give-me gesture relative to when it was presented as an inverted hand shape. Experiment 2 revealed that infants’ goal-directed gaze shifts were not based on different affordances of the two receiving hands. Two additional control experiments further demonstrated that differences in infants’ online gaze behavior were not mediated by an attentional preference for the give-me gesture. Together, our findings provide evidence that properties of social action goals influence infants’ online gaze during action observation. The current studies demonstrate that infants have expectations about well-formed object transfer actions between social agents. We suggest that 12-month-olds are sensitive to social goals within the context of give-and-take interactions while observing from a third-party perspective.
Keywords: Give-me gesture; Infant; Anticipation; Eye movement; Gesture; Social interaction

Designing interaction routines in service networks: A modularity and social construction-based approach - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuss, Jens (Scandinavian Journal of Information Systems)
Keywords: Business process management; Conceptual modeling; Interaction routines; Modular design; Service networks; Social construction

Influence and Dissemination Of Sentiments in Social Network Communication Patterns - Hillmann, Robert; Trier, Matthias (ECIS 2013 Proceedings)
Previous research suggests the existence of sentiments in online social networks. In comparison to real life human interaction, in which sentiments have been shown to have an influence on human behaviour, it is not yet completely understood which mechanisms explain how sentiments influence users in online environments. We develop a theoretical framework that tries to bridge the gap between social influence theories that focus on offline interactions on one hand and online interaction in social networks on the other hand. We then test our hypothesis about the influence and dissemination of sentiments in a quantitative analysis that is based on retrieved textual messages of communication patterns in over 12000 online social networks. Our empirical results suggest a general influence of sentiments on node communication patterns that is evidenced by increased occurrences of subsequent messages that express the same sentiment polarization. We interpret these findings and suggest future research to advance our currently limited theories that assume perceived and generalized social influence to path-dependent social influence models that consider actual behaviour.
Keywords: Social Network Analysis; Sentiment Analysis; Communication Patterns

Numerical Representations and User Behaviour in Social Networking Sites: Towards a Multi- Theoretical Research Framework - Sjöklint, Mimmi; Constantiou, Ioanna; Trier, Matthias (ECIS 2013 Proceedings)
The new technological enhancements and the accessibility to varieties of online applications, enable users to collect personal data and perform self-evaluation through test, comparison and experimentation. The sparked interest in numbers and numbers as self-representative visualisations is prominent in social networking sites, which are the empirical setting for the present study. This paper sets out to establish a multi-theoretical framework which enables the investigation of emerging phenomena of the role of numbers in social networking sites. The proposed framework rests on three theoretical pillars: self-determination theory, heuristic decision making and behavioural economics. A discussion departs from these convictions to investigate user reactions and behaviour when faced with numerical representations in the SNS.
Keywords: User Behaviour; Social Networking Sites; Numerical Representations; Multi-Theoretical Framework; Quantified Self; Pointification

External governance outcome and microfinance success - Uhde, André; Müller, Oliver (International Journal of Monetary Economics and Finance)
Employing a Hausman–Taylor instrument variable (HT–IV) estimator to data from 558 microfinance institutions (MFIs) in 80 developing countries for the period from 2002 to 2007, this paper provides empirical evidence for a positive impact of a country's external governance quality and outcome on local microbanks' economic success in terms of profitability and sustainability. Evidence as well suggests a negative relationship between external governance and the microbanks' social success measured by the depth of outreach. In this context, our analysis reveals that a country's political stability, governance effectiveness, regulatory quality and rule of law are significant key elements of external governance affecting the MFIs' functional performance. Moreover, results from sensitivity analyses indicate that the relationship between external governance quality and microfinance functional performance significantly depends on the microbanks' business concepts, their lending methodologies and sources of funding.
Keywords: microfinance; external governance; economic success; social success; developing countries; profitability; sustainability; microbanks; outreach; political stability; governance effectiveness; regulatory quality; rule of law; governance quality; lending methodologies; funding sources

Educating attention: recruiting, maintaining, and framing eye contact in early natural mother-infant interactions - Nomikou, Iris; Rohlfing, Katharina; Szufnarowska, Joanna (Interaction Studies)
In a longitudinal naturalistic study, we observed German mothers interacting with their infants when they were 3 and 6 months old. Pursuing the idea that infants’ attention is socialized in everyday interactions, we explored whether eye contact is reinforced selectively by behavioral modification in the input provided to infants. Applying a microanalytical approach focusing on the sequential organization of interaction, we explored how the mother draws the infant’s attention to herself and how she tries to maintain attention when the infant is looking at her. Results showed that eye contact is reinforced by specific infant-directed practices: interrogatives and conversational openings, multimodal stimulation, repetition, and imitation. In addition, these practices are contingent on the infant’s own behavior. By comparing the two data points (3 and 6 months), we showed how the education of attention evolves hand-in-hand with the developing capacities of the infant.
Keywords: interactional adaptation; multimodal input; social learning; ecology of attention; eye contact

How to Assess and Study the Cultural Dimension of Social Interactions in Higher Education Institutions (HEI) - Gebhardt, Anja; Jenert, Tobias
Keywords: learning culture; social interaction

Sentiment Polarization and Balance among Users in Online Social Networks - Hillmann, Robert; Trier, Matthias (AMCIS 2012 Proceedings)
Communication within online social network applications enables users to express and share sentiments electronically. Existing studies examined the existence or distribution of sentiments in online communication at a general level or in small-observed groups. Our paper extends this research by analyzing sentiment exchange within social networks from an ego-network perspective. We draw from research on social influence and social attachment to develop theories of node polarization, balance effects and sentiment mirroring within communication dyads. Our empirical analysis covers a multitude of social networks in which the sentiment valence of all messages was determined. Subsequently we studied ego-networks of focal actors (ego) and their immediate contacts. Results support our theories and indicate that actors develop polarized sentiments towards individual peers but keep sentiment in balance on the ego-network level. Further, pairs of nodes tend to establish similar attitudes towards each other leading to stable and polarized positive or negative relationships
Keywords: Social Network Analysis; Ego-Network Analysis; Node Polarization; Sentiment Dissemination

Dissemination Patterns and Associated Network Effects of Sentiments in Social Networks - Hillmann, Robert; Trier, Matthias (Proceedings of the 2012 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining)
Communication in online social networks has been analyzed for some time regarding the expression of sentiments. So far, very little is known about the relationship between sentiments and network emergence, dissemination patternsand possible differences between positive and negative sentiments. The dissemination patterns analyzed in this study consist of network motifs based on triples of actors and the ties among them. These motifs are associated with common social network effects to derive meaningful insights about dissemination activities. The data basis includes several thousand social networks with textual messages classified according to embedded positive and negative sentiments. Based on this data, sub-networks are extracted and analyzed with a dynamic network motif analysis to determine dissemination patterns and associated network effects. Results indicate that the emergence of digital social networks exhibits a strong tendency towards reciprocity, followed by the dominance ofhierarchy as an intermediate step leading to social clustering with hubs and transitivity effects for both positive and negative sentiments to the same extend. Sentiments embedded in exchanged textual messages do only play a secondary role in network emergence and do not express differences regarding the emergence of network patterns.
Keywords: Social Network Analysis; Dynamic Network Motif Analysis; Sentiment Dissemination; Networking Effects; Triads

Generation and evaluation of communicative robot gesture - Salem, Maha; Kopp, Stefan; Wachsmuth, Ipke; Rohlfing, Katharina; Joublin, Frank (International Journal of Social Robotics, Special Issue on Expectations, Intentions, and Actions)
How is communicative gesture behavior in robots perceived by humans? Although gesture is crucial in social interaction, this research question is still largely unexplored in the field of social robotics. Thus, the main objective of the present work is to investigate how gestural machine behaviors can be used to design more natural communication in social robots. The chosen approach is twofold. Firstly, the technical challenges encountered when implementing a speech-gesture generation model on a robotic platform are tackled. We present a framework that enables the humanoid robot to flexibly produce synthetic speech and co-verbal hand and arm gestures at run-time, while not being limited to a predefined repertoire of motor actions. Secondly, the achieved flexibility in robot gesture is exploited in controlled experiments. To gain a deeper understanding of how communicative robot gesture might impact and shape human perception and evaluation of human-robot interaction, we conducted a between-subjects experimental study using the humanoid robot in a joint task scenario. We manipulated the non-verbal behaviors of the robot in three experimental conditions, so that it would refer to objects by utilizing either (1) unimodal (i.e., speech only) utterances, (2) congruent multimodal (i.e., semantically matching speech and gesture) or (3) incongruent multimodal (i.e., semantically non-matching speech and gesture) utterances. Our findings reveal that the robot is evaluated more positively when non-verbal behaviors such as hand and arm gestures are displayed along with speech, even if they do not semantically match the spoken utterance.
Keywords: Social Human-Robot Interaction; Multimodal Interaction and Conversational Skills; Robot Companions and Social Robots; Non-verbal Cues and Expressiveness

Generation and evaluation of communicative robot gesture - Salem, Maha; Kopp, Stefan; Wachsmuth, Ipke; Rohlfing, Katharina; Joublin, Frank (International Journal of Social Robotics, Special Issue on Expectations, Intentions, and Actions)
How is communicative gesture behavior in robots perceived by humans? Although gesture is crucial in social interaction, this research question is still largely unexplored in the field of social robotics. Thus, the main objective of the present work is to investigate how gestural machine behaviors can be used to design more natural communication in social robots. The chosen approach is twofold. Firstly, the technical challenges encountered when implementing a speech-gesture generation model on a robotic platform are tackled. We present a framework that enables the humanoid robot to flexibly produce synthetic speech and co-verbal hand and arm gestures at run-time, while not being limited to a predefined repertoire of motor actions. Secondly, the achieved flexibility in robot gesture is exploited in controlled experiments. To gain a deeper understanding of how communicative robot gesture might impact and shape human perception and evaluation of human-robot interaction, we conducted a between-subjects experimental study using the humanoid robot in a joint task scenario. We manipulated the non-verbal behaviors of the robot in three experimental conditions, so that it would refer to objects by utilizing either (1) unimodal (i.e., speech only) utterances, (2) congruent multimodal (i.e., semantically matching speech and gesture) or (3) incongruent multimodal (i.e., semantically non-matching speech and gesture) utterances. Our findings reveal that the robot is evaluated more positively when non-verbal behaviors such as hand and arm gestures are displayed along with speech, even if they do not semantically match the spoken utterance.
Keywords: Social Human-Robot Interaction; Multimodal Interaction and Conversational Skills; Robot Companions and Social Robots; Non-verbal Cues and Expressiveness

Tutor spotter: Proposing a feature set and evaluating it in a robotic system - Lohan, Katrin Solveig; Rohlfing, Katharina; Pitsch, Karola; Saunders, Joe; Lehmann, Hagen; Nehaniv, Chrystopher L.; Fischer, Kerstin; Wrede, Britta (International Journal of Social Robotics)
Keywords: Social Robots; Contingency

SCM - A Simple, Modular and Flexible Customer Interaction Management System - Schuster, Jörg; Lee, Yeong Su; Kobothanassi, Despina; Bargel, Matthias; Geierhos, Michaela (International Conference on Information Society (i-Society 2011))
SCM is a simple, modular and flexible system for web monitoring and customer interaction management. In our view, its main advantages are the following: It is completely web based. It combines all technologies, data, software agents and human agents involved in the monitoring and customer interaction process. It can be used for messages written in any natural language. Although the prototype of SCM is designed for classifying and processing messages about mobile-phone related problems in social networks, SCM can easily be adapted to other text types such as discussion board posts, blogs or emails. Unlike comparable systems, SCM uses linguistic technologies to classify messages and recognize paraphrases of product names. For two reasons, product name paraphrasing plays a major role in SCM: First, product names typically have many, sometimes hundreds or thousands of intralingual paraphrases. Secondly, product names have interlingual paraphrases: The same products are often called or spelt differently in different countries and/or languages. By mapping product name variants to an international canonical form, SCM allows for answering questions like Which statements are made about this mobile phone in which languages/in which social networks/in which countries/...? The SCM product name paraphrasing engine is designed in such a way that standard variants are assigned automatically, regular variants are assigned semiautomatically and idiosyncratic variants can be added manually. With this and similar features we try to realize our philosophy of simplicity, modularity and flexibility: Whatever can be done automatically is done automatically. But manual intervention is always possible and easy and it does not conflict in any way with the automatic functions of SCM.
Keywords: Social Media Business Integration; Contact Center Application Support; Monitoring Social Conversations; Social Customer Interaction Management; Monitoring; Software Agents

Processing Multilingual Customer Contacts via Social Media - Geierhos, Michaela; Lee, Yeong Su; Bargel, Matthias (Multilingual Resources, Multilingual Applications: Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we will describe a new approach to customer interaction management by integrating social networking channels into existing business processes. Until now, contact center agents still read these messages and forward them to the persons in charge of customer’s in the company. But with the introduction of Web 2.0 and social networking clients are more likely to communicate with the companies via Facebook and Twitter instead of filling data in contact forms or sending e-mail requests. In order to maintain an active communication with international clients via social media, the multilingual consumer contacts have to be categorized and then automatically assigned to the corresponding business processes (e.g. technicalservice, shipping, marketing, and accounting). This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer relationship management.
Keywords: Classification of Multilingual Customer Contacts; Contact Center Application Support; Social Media Business Integration

Customer Interaction 2.0: Adopting Social Media as Customer Service Channel - Geierhos, Michaela (Journal of Advances in Information Technology)
Since customers first share their problems with a social networking community before directly addressing a company, social networking sites such as Facebook, Twitter, MySpace or Foursquare will be the interface between customer and company. For this reason, it is assumed that social networks will evolve into a common communication channel – not only between individuals but also between customers and companies. However, social networking has not yet been integrated into customer interaction management (CIM) tools. In general, a CIM application is used by the agents in a contact centre while communicating with the customers. Such systems handle communication across multiple different channels, such as e-mail, telephone, Instant Messaging, letter etc. What we do now is to integrate social networking into CIM applications by adding another communication channel. This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer service management and the company’s response will be delivered through the customer’s preferred social networking site.
Keywords: Social Media Business Integration; Multichannel Customer Interaction Management; Contact Centre Application Support

Mindful tutors: Linguistic choice and action demonstration in speech to infants and a simulated robot - Fischer, Kerstin; Foth, Kilian; Rohlfing, Katharina; Wrede, Britta (Interaction Studies)
It has been proposed that the design of robots might benefit from interactions that are similar to caregiver–child interactions, which is tailored to children’s respective capacities to a high degree. However, so far little is known about how people adapt their tutoring behaviour to robots and whether robots can evoke input that is similar to child-directed interaction. The paper presents detailed analyses of speakers’ linguistic and non-linguistic behaviour, such as action demonstration, in two comparable situations: In one experiment, parents described and explained to their nonverbal infants the use of certain everyday objects; in the other experiment, participants tutored a simulated robot on the same objects. The results, which show considerable differences between the two situations on almost all measures, are discussed in the light of the computer-as-social-actor paradigm and the register hypothesis.
Keywords: human–robot interaction (HRI); social communication; register theory; motionese; robotese; child-directed speech (CDS); motherese; mindless transfer; computers-as-social-actors

Language Does Something: Body Action and Language in Maternal Input to Three-Month-Olds - Nomikou, Iris; Rohlfing, Katharina (IEEE Transactions on Autonomous Mental Development)
Keywords: acoustic packaging; mother-child interaction; social learning; multimodal grounding in input; ecology of interactions; synchrony

Developing feedback: How children of different age contribute to a tutoring interaction with adults - Vollmer, Anna-Lisa; Pitsch, Karola; Lohan, Katrin Solveig; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (Development and Learning (ICDL), 2010 IEEE 9th International Conference on Development and Learning)
Keywords: tutoring interaction; social interaction; video signal processing; robot systems; paediatrics; neurophysiology; Learning; infant; feedback; biology computing; cognitive capabilities; cognition; children

People modify their tutoring behavior in robot-directed interaction for action learning - Vollmer, Anna-Lisa; Lohan, Katrin Solveig; Fischer, Kerstin; Nagai, Yukie; Pitsch, Karola; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (Development and Learning, 2009. ICDL 2009. IEEE 8th International Conference on Development and Learning)
In developmental research, tutoring behavior has been identified as scaffolding infants' learning processes. It has been defined in terms of child-directed speech (Motherese), child-directed motion (Motionese), and contingency. In the field of developmental robotics, research often assumes that in human-robot interaction (HRI), robots are treated similar to infants, because their immature cognitive capabilities benefit from this behavior. However, according to our knowledge, it has barely been studied whether this is true and how exactly humans alter their behavior towards a robotic interaction partner. In this paper, we present results concerning the acceptance of a robotic agent in a social learning scenario obtained via comparison to adults and 8-11 months old infants in equal conditions. These results constitute an important empirical basis for making use of tutoring behavior in social robotics. In our study, we performed a detailed multimodal analysis of HRI in a tutoring situation using the example of a robot simulation equipped with a bottom-up saliency-based attention model. Our results reveal significant differences in hand movement velocity, motion pauses, range of motion, and eye gaze suggesting that for example adults decrease their hand movement velocity in an Adult-Child Interaction (ACI), opposed to an Adult-Adult Interaction (AAI) and this decrease is even higher in the Adult-Robot Interaction (ARI). We also found important differences between ACI and ARI in how the behavior is modified over time as the interaction unfolds. These findings indicate the necessity of integrating top-down feedback structures into a bottom-up system for robots to be fully accepted as interaction partners.
Keywords: robot simulation; hand movement velocity; robotic interaction partner; robotic agent; robot-directed interaction; multimodal analysis; Motionese; Motherese; intelligent tutoring systems; immature cognitive capability; human computer interaction; eye gaze; child-directed speech; child-directed motion; bottom-up system; bottom-up saliency-based attention model; adult-robot interaction; adult-child interaction; adult-adult interaction; human-robot interaction; action learning; social learning scenario; social robotics; software agents; top-down feedback structures; tutoring behavior

Rezension zu Alfred K. Treml „Warum der Berg ruft. Bergsteigen aus evolutionstheoretischer Sicht“ - Meier, Heiko (Sport und Gesellschaft)
Keywords: Philosophy; Social Sciences (miscellaneous); History

Social Capital - Landhäußer, Sandra; Ziegler, Holger (Social Work & Society)
In the broadest sense social capital reflects the idea of resources rooting in relations between individuals resp. in the embeddings of people in groups, associations, communities and even societies. A central assumption is that social capital - as a resource - is emerging from the quality of these relationships. This quality may be described in a more materialistic sense because these relations open up access to specific resources or assets. But it may also be imbued with valuated connotations, in particular referring to the essential contribution of networks and trust in promoting well-being, a sense of belonging and decency as individuals in entities blessed with social capital are pretended to engage in mutually beneficial collective actions. Therefore social capital applies to peoples’ shared expectations, norms, values, and beliefs, their commitments to each other and eventually their associative capacities to knit the ‘social fabric’.
Keywords: Social Capital

Social Work and the Quality of Life Politics - A Critical Assessment - Landhäußer, Sandra; Ziegler, Holger (Social Work & Society)
The feature of this paper is a critical assessment of the current discourses about quality of life (QoL) and their implications for Social Work. At first it pictures some major historical backgrounds of the discussion on the improvement of life quality as an aim of societal development. In particular three crucial shifts in the politics of QoL - its 'individualisation', its 'informalisation' and its 'culturalisation' - and their implications for Social Work are critically examined theoretically and empirically referring to the results of an own community-study. The paper concludes with an alternative suggestion reflecting the idea of an 'autonomy-based' approach of democratic equality.
Keywords: Critical; quality; Social